1997
DOI: 10.1080/016502597384794
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Everyday Family Life: The Development of Social Rules in Mother-Child and Sibling Relationships

Abstract: The aims of this study were: (1) to characterise changes in the frequency and kind of social rules used in mother-child and sibling relationships over a 14-month period; (2) to assess the degree to which conflict functioned as a forum for social rules; and (3) to describe the nature of the association between references to social rules and the quality of family relationships. Naturalistic home observations of 47 families were conducted when focal younger siblings were 33 and 47 months of age. Family conversati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 36 publications
0
26
0
8
Order By: Relevance
“…No study has addressed the question of which rules are more frequently mentioned by children while playing the roles of adults. For example, it is possible that while playing the roles of mothers girls discuss conventional rather than moral rules, as real mothers have been found to do (Piotrowski, 1997;Smetana, 1993).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…No study has addressed the question of which rules are more frequently mentioned by children while playing the roles of adults. For example, it is possible that while playing the roles of mothers girls discuss conventional rather than moral rules, as real mothers have been found to do (Piotrowski, 1997;Smetana, 1993).…”
mentioning
confidence: 96%
“…The results of these studies suggest that the contribution of parents and peers to children's social development seems to differ by conceptual domains. Mothers have been found to discuss conventional rules more often, whereas siblings focus more on moral rules (Piotrowski, 1997;Smetana, 1993). Furthermore, observational studies have shown that parents of differently aged children vary in their concern about different domains (Gralinski & Kopp, 1993;Smetana, 1989) and that they respond differently to social transgressions in different domains (see Smetana, 1997, for a review).…”
mentioning
confidence: 97%
See 3 more Smart Citations